Respon Adaptif Pertumbuhan dan Produksi Beberapa Varietas Padi Merah Lokal terhadap Cekaman Salinitas - Siregar, Mawaddah Putri Arisma; Harahap, Evi Julianita; Junita, Dewi; Afrillah, Muhammad; Sari, Putri Mustika (Jurnal Agrotek Lestari, 2025)
Brown rice is recognized as a food commodity with high nutritional value and considerable health benefits for humans. However, its cultivation remains relatively limited in popularity and is often associated with low productivity, particularly when grown on marginal lands such as coastal areas affected by high salinity. This study aimed to evaluate the adaptive responses in growth and yield performance of several local brown rice genotypes under salinity stress conditions in the coastal region of Pantai Cermin, Serdang Bedagai Regency, North Sumatra. The research was conducted using a non-factorial Randomized Block Design (RBD) involving eight local brown rice genotypes: Beras Merah, Sidrap Merah, Kelik-3, Mesuji, Sijior, Sipenget, Meulaboh, and Si Tappe. The observed parameters included plant height, number of leaves, number of tillers, number of productive tillers, root fresh weight, root length, grain weight, and panicle length. The results indicated that varietal treatments had a statistically significant effect on all observed parameters, except for the number of leaves. The Sijior genotype exhibited the greatest plant height (58.22 cm), while the Meulaboh genotype recorded the highest values for the number of tillers (29.3), number of productive tillers (28.0), and root length (20.7 cm). The Kelik-3 genotype demonstrated the highest root fresh weight (173.3 g), whereas the Si Tappe genotype showed superior performance in grain weight (62.0 g) and panicle length (31.7 cm).Overall, comprehensive analysis of the data suggests that the Si Tappe, Beras Merah, Kelik-3, and Meulaboh genotypes exhibited the most favorable adaptive responses and demonstrated a high degree of tolerance to salinity stress. The robust root development observed in the Meulaboh and Kelik-3 genotypes supports their adaptability to saline environments, while the extended panicle length in Si Tappe positively contributed to enhanced grain weight.